Metal Oxides of Group 4: General Insights and the Synthesis of ZrO2/HfO2 and ZrO2:Eu/ZrO2 Core/Shell Nanocrystals - Carlotta Seno (CHIMIA)
Metal oxide nanocrystals, like ZrO2 and HfO2, serve as hosts for optically active lanthanide ions. However, synthesizing colloidally stable nanocrystals with complex architectures remains challenging. We have pioneered the synthesis of metal oxide core/shell nanocrystals, where HfO2 epitaxially grows onto ZrO2. The beneficial effect of the shell on the optical properties is demonstrated by investigating the photoluminescence of ZrO2:Eu and of ZrO2:Eu/ZrO2 after growing a protective zirconia shell on it.[1]